Effect of maturity stages on physical properties of cocoa (Theobroma cacao L.) pods - Oluwamayokun Soyoye, Babatunde; Mat Nawi, Nazmi; Zulkifli, Mohamad Ariffin; Chen, Guangnan; Madian, Nurfadzilah; Mokhtar, Ahmad Faiz; Adam, Siti Nooradzah; Al Riza, Dimas Firmanda (Universiti Putra Malaysia Press, 2024)
Cocoa is one of the main plantation crops in Malaysia. Significant efforts have been made to modernise the industry using mechanisation and automation technologies. Thus, determination of the physical properties of cocoa pods at different maturity stages is paramount for an appropriate design and development of a post-harvest machinery system for pod breaking, sorting and grading. This study investigated the effect of five different maturity stages (unripe, under-ripe, ripe, very-ripe and over-ripe) on the physical properties of cocoa pods. A total of 80 cocoa pods (Clone PBC140) were used as samples, where 16 pods represented each maturity stage. For the unripe stage, the largest mean dimensional values were 172.45, 89.3 and 111.18 mm for the pods’ length, diameter and geometric mean diameter, respectively. The highest mean values of 0.66 and 0.54 for the over-ripe stage were recorded for sphericity and aspect ratio, respectively. The geometric mean diameter, weight and firmness were found to be inversely proportional to the maturity stages. The advanced maturity stages experience greater colour intensity, as reflected in the chroma (C*) and higher L*, a* and b* values. This study has found that the colour and texture of the cocoa pods change throughout their maturity. In conclusion, the results reported in this study can be used as a reference for designing and developing a machinery system for post-harvest fruit processing.